Exposure to cumulative stressors affects the laying phenology and incubation behaviour of an Arctic-breeding marine bird - Smith, Reyd A.; Albonaimi, Saya S.; Hennin, Holly L.; Gilchrist, H. Grant; Fort, Jérôme; Parkinson, Kyle J.L.; Provencher, Jennifer F.; Love, Oliver P. (Science of The Total Environment, 2022)
Wildlife are exposed to multiple stressors across life-history stages, the effects of which can be amplified as human activity surges globally. In Arctic regions, increasing air and ocean temperatures, more severe weather systems, and exposure to environmental contaminants all represent stressors occurring simultaneously. While Arctic vertebrates, including marine birds, are expected to be at risk of adverse effects from these individual stressors, few studies have researched their combined impacts on breeding behaviour and reproductive success. The interactive effects of environmental conditions and mercury (Hg) contamination on laying phenology and incubation behaviour were examined in female common eiders (Somateria mollissima, mitiq, ᒥᑎᖅ ᐊᒪᐅᓕᒡᔪᐊᖅ) nesting at Canada's largest Arctic breeding colony. Conditions with higher pre-breeding air temperatures were linked to females with higher egg Hg concentrations laying earlier than those with lower Hg values. Furthermore, examination of a total of 190 days of incubation behaviour from 61 eiders across two years revealed a negative relationship between wind speed and the frequency of incubation interruptions. Importantly, exposure to higher air temperatures combined with lower Hg concentrations was significantly correlated with increased incubation interruptions. Although previous research has shown that warmer spring temperatures could afford lower quality females more time to improve body condition to successfully lay, results suggest these females may face stronger cumulative fitness costs during incubation in warmer years, potentially in combination with the effects of Hg on physiological stress and hormone secretion. This study highlights how multiple stressors exposure, driven by human-induced environmental changes, can have a complex influence on reproduction.